Ораторское искусство в процессе изучения иностранного языка в информационном обществе - Kossakowska-Maras, Maria (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
One of the primary objectives of education today is the training of specialists with expertise not only in the field of natural sciences and engineering, but also knowledge in the field of business communication, able to enjoy all the richness of the literary language, and, what’s more, striving for continuous personal and professional growth. Nowadays the audiovisual instruments of communication they have become the main carrier of information and it affected the cognitive style of persons living in information age: today researches the mosaic style of thinking of contemporary individuals and clip thinking.
Keywords: ораторское искусство; культура речи; клиповое мышление; информационное общество; oratory; culture of speech; clip thinking; information society